Examining job involvement and perceived organizational support toward organizational commitment: job insecurity as mediator - Hngoi, Chin Ling; Abdullah, Nurul-Azza; Wan Sulaiman, Wan Shahrazad; Zaiedy Nor, Norshaffika Izzaty (Frontiers in Psychology, 2024)
This study delves into the intricate relationships among job involvement (JI), perceived organizational support (POS), job insecurity (JIS), and organizational commitment (OC), with a particular focus on the mediating role of JIS within the context of the Malaysian private sector. The research delves into the antecedents of job insecurity and organizational commitment, offering insights to enhance commitment. Our study involved 440 employees in the Malaysian private sector, utilizing self-report questionnaires administered online. Notably, our findings underscore the significance of employment flexibility, job positions, and tenure in shaping JIS. Furthermore, we identify significant relationships among the variables: POS negatively predicts JIS, while JI, JIS, and POS collectively predict OC, with JIS partially mediating the POS-OC relationship. These empirically-grounded insights offer actionable guidance for organizations, empowering human resources practitioners to craft effective talent retention strategies and allocate resources strategically. In doing so, organizations can enhance employee productivity and bolster organizational commitment, ultimately contributing to sustained success in a dynamic work environment. These findings hold valuable implications for human resources practitioners, guiding the development of talent retention strategies and resource allocation to enhance employee productivity.